2015
DOI: 10.1016/j.physa.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

How can one explain changes in the monthly pattern of suicide?

Abstract: International audienceThe monthly pattern of suicides has remained a puzzle ever since it was discovered in the second half of the 19th century. In this paper we intend to “explain” not the pattern itself but rather its changes across countries and in the course of time.First, we show that the fairly common idea according to which this pattern is decaying in “modern” societies is not altogether true. For instance, around 2000, in well urbanized countries like South Korea or Spain this pattern was still as stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…Cabe pensar que en este aspecto hay implicados diversos factores de tipo geográfico, climático, cultural y personal (biológicos y psicológi-cos), que operan interactivamente. En este estudio, las demandas por conducta suicida se dieron más significativamente en agosto y diciembre, en tanto que la mayoría de las publicaciones suelen hablar de la primavera o inicio del verano y apenas en diciembre 6,29,30 . También la conducta suicida se dio más frecuentemente por la tarde, en comparación con las demandas físicas y psiquiá-tricas.…”
Section: Discussionunclassified
“…Cabe pensar que en este aspecto hay implicados diversos factores de tipo geográfico, climático, cultural y personal (biológicos y psicológi-cos), que operan interactivamente. En este estudio, las demandas por conducta suicida se dieron más significativamente en agosto y diciembre, en tanto que la mayoría de las publicaciones suelen hablar de la primavera o inicio del verano y apenas en diciembre 6,29,30 . También la conducta suicida se dio más frecuentemente por la tarde, en comparación con las demandas físicas y psiquiá-tricas.…”
Section: Discussionunclassified
“…Abundant research dating back to the 19th century demonstrates seasonal suicide patterns, with an increase in spring and a decrease in winter (Durkheim, 1897 ; Maes et al ., 1993 ; Chew and McCleary, 1995 ; Ajdacic-Gross et al ., 2010 ; Christodoulou et al ., 2012 ; Woo et al ., 2012 ; Roehner, 2015 ; Dixon and Kalkstein, 2018 ; Yang et al ., 2019 ). While the pattern of seasonal suicides has been confirmed in many countries, the mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship between suicides and the effects of the physical external environment has been recognized in documents dating back to the 19 th century [ 7 ], including seasonality, which refers to the fact that suicides have a monthly pattern which tends to repeat yearly [ 8 ]. The seasonality of suicide has been studied based on two broad perspectives, biological and sociological.…”
Section: Introductionmentioning
confidence: 99%
“…Studying suicide from a sociological perspective, Durkheim (1897) [ 11 ] proposed an opposing theory that increased social activity during spring and summer creates more social stress, and this could lead to suicidal behavior when unable to psychologically cope with the frustration caused by failed social interactions, especially for people with depression [ 9 , 12 , 13 ]. More recent studies of suicides have shown seasonal patterns in different regions and countries, such as the review by Roehner of data from France, Ireland, South Korea and Switzerland [ 8 ]. A study by Petridou, et al .…”
Section: Introductionmentioning
confidence: 99%